Motive, attachment and fan behavioural intention in sport tourism event: empirical study of formula one motorsport / Mohd Helme Basal - Basal, Mohd Helme (2014)
For the past ten years, motorsports has been recognised as one of the famous sporting events being organized. Hundred thousand of fans watch the event live and million others around the world watch the race through live broadcasting. In 2010 alone, 527 million fans around the world watched the 2010 FIA Formula One Grand Prix. As a result, motorsport event has significantly benefitted many parties in term of social, economy, and advanced technology. The impact has also paved ways for sport marketers and academicians to discover wider academic topics. Nevertheless, there have been evidently few empirical researches being conducted in exploring motive and attachment factor among fans and their behavioural intention in motorsport event setting. This research attempts to fill such a void by examining the relationship among motives, attachment and behavioural intention for future motorsport event. Adopted Motivational Scale for Sport Consumption (2001), Point of Attachment Index (2003), and Intension for Sport Consumption Behavior Scale (ISCBS) questionnaires were used to measure the constructs. Data were collected from 392 respondents who attended the Malaysia Formula 1 race at Sepang International Circuit. Correlation and regression analyses were employed to examine the relationships among the constructs. Confirmatory factor analysis (CFA) was also performed to validate the scales. The relationship between the construct are positive and most of the fans have positive intention towards future event. Fans that are highly motivated and possess high attachment level are more likely to consume future event and purchase related products. Specifically, fans who are motivated by aesthetic value and attached highly to crowd experience show the strongest relationship towards future intention. Attachment was also found to partially mediate the relationship between motive and behavioural intention. These results provide many implications for sport marketers to have better understanding and strategize marketing effort in motorsport event. The findings also offer important insight for future research and management practices.